Upaya Meningkatkan Kemampuan Motorik melalui Pendekatan Permainan pada Peserta Didik Kelas Bawah Sekolah Dasar - Ardianto, Ach Aris Eko; Kuntjoro, Bambang Ferianto Tjahyo; Makung, Yohanes Giovani Pion (MAN Insan Cendekia Jambi, 2024)
Based on the research objectives by looking at the impact of a game approach in improving the motor skills of students, class action research as a method used by using several stages of implementation, the subject in the study with lower grade students of Putat Gede I/94 Surabaya public elementary school, the instrument uses a motor skill test with agility, coordination, balance and speed. Data obtained and analysed by descriptive with percentage. The results of the study at each stage of the pre-siklus (18.52%), siklus I (37.04%),siklus II (74.07%). That way it can be seen that there is an increase at each stage based on the concept of completeness criteria, so it can be concluded that there is an increase in motor skills through the game approach in students.